2008
DOI: 10.1029/2008gl034724
|View full text |Cite
|
Sign up to set email alerts
|

Supercells and mesocyclones in outer rainbands of Hurricane Katrina (2005)

Abstract: [1] This study documents and describes supercells embedded within the outer rainbands of Hurricane Katrina (2005). Radar reflectivity and velocity data collected on 29 August 2005 by Weather Surveillance Radar 1988 Doppler radars were used to track the supercells. Radar analysis indicates that the supercells were characterized by heavy precipitation collocated with band-relative mesocylonic circulations containing strong vorticity and a wind speed enhancement to their northeast. Atmospheric soundings and dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Indeed, prior studies have demonstrated that offshore environments can be conducive to supercell formation (Bogner et al 2000;Baker et al 2009), documented offshore supercells using coastal Doppler radars (Spratt et al 1997;Rao et al 2005;Lee et al 2008), and noted reports of waterspouts and tornadoes within a few kilometers of the coastline (Gentry 1983;Hagemeyer 1997). This paper contributes to such evidence by providing the first detailed observations of tropical cyclone miniature supercells located more than 100 km offshore and beyond the Doppler range of operational coastal radars.…”
Section: Introductionmentioning
confidence: 77%
“…Indeed, prior studies have demonstrated that offshore environments can be conducive to supercell formation (Bogner et al 2000;Baker et al 2009), documented offshore supercells using coastal Doppler radars (Spratt et al 1997;Rao et al 2005;Lee et al 2008), and noted reports of waterspouts and tornadoes within a few kilometers of the coastline (Gentry 1983;Hagemeyer 1997). This paper contributes to such evidence by providing the first detailed observations of tropical cyclone miniature supercells located more than 100 km offshore and beyond the Doppler range of operational coastal radars.…”
Section: Introductionmentioning
confidence: 77%
“…Inner-core rotating cells (or better known as vortical hot towers) have been investigated within the framework of TC dynamics (e.g., Hendricks et al 2004;Montgomery et al 2006;Fang andZhang 2010, 2011). Conversely, supercells in the outer rainbands-regardless of the underlying surface type-have been studied through the lens of midlatitude severe local storms (e.g., McCaul and Weisman 1996;Suzuki et al 2000;Lee et al 2008;Baker et al 2009;Eastin and Link 2009). Novlan (1973) was among the first to identify strong vertical wind shear as being favorable for TC tornadogenesis and noted the likely importance of the tilting of horizontal vorticity, which was beginning to be appreciated in studies of midlatitude severe convective storms as the source of mesocyclone rotation (e.g., Barnes 1970).…”
Section: Introductionmentioning
confidence: 99%
“…While a strong vertical shear may enhance turbulent mixing, large helicity may reduce turbulence dissipation [Lilly, 1986] and prevent the stormˈs updraft core from diffusing. Furthermore, given that minisupercells are often embedded in outer rainbands [Hill et al, 1966;Spratt et al, 1997;Lee et al, 2008;Mashiko et al, 2009], an entrainment rate may be reduced owing to the two-dimensional configuration of the rainband. It is necessary to perform large eddy simulations of minisupercells under the TC environment, and to directly evaluate ε, as was done for ordinary cells by Romps [2010] and Yeo and Romps [2013].…”
Section: Entrainment Ratementioning
confidence: 99%